The Effect of Discounts on Purchase Decisions on the TikTok Shop Application - Hairil Nurdin; Taqwa Sultan; Maxymilianus Soter Mite Kombong; Grancia Caroline Bria (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This study aims to explore the effect of discounts on purchasing decisions among students of the Department of Business Administration, State Polytechnic of Kupang. The research method used is quantitative with descriptive and associative approaches. Data was collected through a questionnaire distributed to 30 respondents who had made purchases through TikTok Shop. The data was analyzed using SPSS 25. Descriptive analysis showed that the majority of respondents were female students aged 22 – 25 years. The results of a simple linear regression analysis show that discounts have a positive and significant influence on purchase decisions. Contributing to this research, businesses should increase discounts on TikTok shops to increase the potential of potential customers and retain existing customers.